Implementasi Konsep Kiddy Town pada perancangan Day Care untuk anak usia dini di Surabaya - Hartono, Audina Fransisca Maria (Intra, 2016)
Children developments must be considered by parents. This is because during the growth and development both in terms of mental or physical will determine how the child's personality in the future. Sometimes parents have a busy schedule at work, so parents will not be able to monitor and follow the children development to the maximum. This will cause day care become an option to help parents in supervising and providing a good development so focused on their children.Interesting and competent day care can be a target where parents want to leave their children. Through Kiddy Town interior design concept which is to realize the medium play and learning for children. Using a different concept than the others, making children and parents keen to select the day care. By taking the concept of town that provides insight for children to be more informative, creative and learn about the environment. Within this design there will be streets as the city that made the children that are agile to explore the streets in day care. Children will be more independent and daring to explore new roads and can be easily adapted with the atmosphere of a modern city. With this day care presence, it expects to meet the need for facilities for young children to develop the ability of intelligence and creativity. Hopefully this day care design can help parents in caring for their children and can make a positive impact for children.